2019
DOI: 10.3389/fphar.2019.00740
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Plays a Protective Role Against Intravascular Hemolysis-Mediated Acute Kidney Injury

Abstract: Massive intravascular hemolysis is associated with acute kidney injury (AKI). Nuclear factor erythroid-2-related factor 2 (Nrf2) plays a central role in the defense against oxidative stress by activating the expression of antioxidant proteins. We investigated the role of Nrf2 in intravascular hemolysis and whether Nrf2 activation protected against hemoglobin (Hb)/heme-mediated renal damage in vivo and in vitro . We observed renal Nrf2 activation in human hemolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 71 publications
1
34
0
Order By: Relevance
“…Besides CSF analysis, we used a well-established model of acute sterile hemolysis to investigate the formation of the different Hb species in vivo. In agreement with previous observations [27,50,51], we found that the injection of PHZ triggered a marked elevation of extracellular heme content in the plasma. The determination of the distribution of the extracellular heme among the different redox states of Hb revealed that Hb dominates at an early time point (4 h), and hemichrome becomes more dominant at later time points.…”
supporting
confidence: 93%
“…Besides CSF analysis, we used a well-established model of acute sterile hemolysis to investigate the formation of the different Hb species in vivo. In agreement with previous observations [27,50,51], we found that the injection of PHZ triggered a marked elevation of extracellular heme content in the plasma. The determination of the distribution of the extracellular heme among the different redox states of Hb revealed that Hb dominates at an early time point (4 h), and hemichrome becomes more dominant at later time points.…”
supporting
confidence: 93%
“…Previous studies have indicated that the Nrf2 signaling pathway plays a key role in inflammatory responses and oxidative stress during I/R. Nrf2 knockout increases the level of oxidative stress in AKI and exacerbates the ischemic injury, which, when activated, inhibits ROS levels and reduces AKI kidney damage ( Rubio-Navarro et al, 2019 ). Consistently, the increased expression of MDA, SOD and GSH in I/R mice reflects the increase in oxidative stress levels, and SalB treatment has a significant improvement effect, especially in the high-dose group.…”
Section: Discussionmentioning
confidence: 99%
“…The Keap1/Nrf2/p62/SQSTM1 signaling pathway is a major defense mechanism for oxidative stress [29][30][31]. Recent studies indicated that p62/SQSTM1 is a target gene of the transcription factor Nrf2 [32,33].…”
Section: Oxidative Stress-induced By 13-ac Involves the Dysregulationmentioning
confidence: 99%